Transformation of Citizens’ role in Kazakhstan's Public Administration: From Clients to Partners - Abdulla Tokenov (Research Retrieval and Academic Letters, 2024)
Global challenges of contemporary world such as changes in natural disasters and climate change, the cost of living crisis, the risks of a pandemic, terrirism, and confrontation in the geopolitical arena require a consolidated approach to solving them. National governments are increasingly unable to cope with global gaps alone. Therefore, this issue requires a comprehensive approach requiring the participation of all interested parties, including citizens. The role of citizens in the decision-making process has been transformed following changes in public administration models. Usually, public administration theorists identify three models of public administration that developed during certain historical periods. These models include the classical or traditional system, New Public Management, and New Public Service or Public Value Governance.